O português brasileiro em gramáticas de linguistas - Aguiar, Ana Gabriella Barbosa Silva de (2020)
Between the late 1970s and early 1980s, brazilian linguists developed a series of collective works, all aimed on describing the language that was spoken in Brazil. Before such period, this kind of research was rare; and restricted to the works of linguists, philologists and dialectologists in their own local and institutional contexts. It is possible to mention the following studies from that time: Dialeto Caipira, by Amaral (1920), and the Atlas Prévio dos Falares Baianos, by Nelson Rossi (1960-62). These early studies paved the way for projects such as the Cultured Oral Urban Standard Project and the Spoken Portuguese Grammar Project, to begin unveiling the language spoken in Brazil between the late 1970s and early 1980s. The seeds of these projects germinated, fruited and brought to light a variety of results. Consequently, brazilian linguists began to develop a series of contemporary grammars in the first decades of the 21st century. These instruments were based on the theoretical and methodological bases of linguistic science, which shed new light on the syntactic, semantic and discursive phenomena, resizing the metalinguistic work elaborated by tradition (FARACO; VIEIRA, 2016). Amongst these grammars, there are those that legitimize and promote Brazilian Portuguese as an autonomous language, not just as a variation of European Portuguese. Therefore, the present study focuses on the Brazilian Portuguese grammars, in order to investigate the perceival of the standard portuguese within the linguists' grammars and the correlations between the concept of standard portuguese and the notion of Brazilian Portuguese defended within these instruments. For this purpose, the studies of Bagno (2012), Castilho (2014) and Perini (2017) were selected, entitled, respectively, Gramática pedagógica do português brasileiro, Nova gramática do português brasileiro and Gramática descritiva do português brasileiro. Thereby, some concepts attributed to the standard language by Linguistics were rescued (COSERIU, 1979; FARACO, 2008; MONTEAGUDO, 2011; RAJAGOPALAN, 2011; BAGNO, 2012) and, after this rescue, it was returned to retrospection in order to bring to the present the speeches, debates and projects elaborated in the past about Brazilian Portuguese. Therefore, this dissertation is inserted in área of the Applied Linguistics (LOPES, 2006; MENEZES; GOMES, 2009) with an interface in the Linguistics Historiography (KOENER, 1996, 2014; SWIGGERS, 2010; ALTMAN, 2012; BATISTA, 2016). Through Applied Linguistics and Historiography of Linguistics, this research intends, when selecting brazilian portuguese grammars, to observe them on two fronts: the first, focused on the analysis of the introductory chapters, and the second, focused on the chapters concerning concordance verbal. Observing these two fronts allows this study to have a view of the contemporary brazilian portuguese grammars, as both the discourses and the materialization of Brazilian Portuguese, through the syntactic phenomenon of concordance, allow for an understanding of the functioning of the Brazilian language. In this way, it is concluded that the concept of standard language present in grammars impacts the notion of Brazilian Portuguese disseminated and promoted within the instruments, since this notion is crossed by the selection of standards resulting from the grammatization work performed by linguists. In the case of concordance verbal, for example, the contemporary grammars of brazilian portuguese present convergences on the syntactic behavior of this phenomenon, however there are also differences, which are closely related to theoretical and methodological choices, as well as the choice of the corpus for the recognition of the brazilian portuguese standard(s).